Analisis Stabilisasi Bioetanol Terhadap Korosi Logam Menggunakan Inhibitor Alami Berbasis Minyak Pala - Nisrina, Hernita Zaida; Alya, Nazwa; Ramadhan, Rizky Setiawan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This research evaluates the potential of nutmeg essential oil as an environmentally friendly corrosion inhibitor for carbon steel in a bioethanol medium. GC-MS analysis identified 23 compounds, with the major components including sabinene (21.3%), α-pinene (18.7%), β-pinene (12.4%), myristicin (8.9%), and limonene (7.2%). Weight loss testing over 90 days showed the control system had a corrosion rate of 2.847 mm/year, which significantly decreased to 0.412 mm/year with the addition of 750 ppm nutmeg oil, resulting in an optimal inhibition efficiency of 85.5%. Increasing the concentration to 1000 ppm did not provide a significant improvement, indicating adsorption saturation on the metal surface. Electrochemical characterization thru potentiodynamic polarization curves showed a shift in corrosion potential from -0.687 V to -0.523 V and a decrease in corrosion current density from 48.3 μA/cm² to 6.8 μA/cm² at the optimal concentration, confirming nutmeg oil as a mixed-type inhibitor. Electrochemical impedance spectroscopy showed an increase in polarization resistance from 245 Ω·cm² to 1,687 Ω·cm², consistent with the weight loss data.